Solar Radiation Effects on Dry Matter Accumulations and Transfer in Maize - Yang, Yunshan; Guo, Xiaoxia; Liu, Guangzhou; Liu, Wanmao; Xue, Jun; Ming, Bo; Xie, Ruizhi; Wang, Keru; Hou, Peng; Li, Shaokun (Frontiers in Plant Science, 2021)
Solar radiation is the energy source for crop growth, as well as for the accumulation, distribution and transfer characteristics of photosynthetic products that determine maize yield. Therefore, learning the effects of different solar radiation amounts on maize growth is especially important. The present study focused on the quantitative relationships between solar radiation amounts and dry matter (photosynthetic products) accumulations and distributions in maize. We chose the region with the highest solar radiation in China to conduct shading experiments under different planting densities. The results showed that the yields of the commonly planted cultivars XY335 and ZD958 at S1, S2 and S3 (increasing shade treatments) were 7.3%, 21.2% and 57.6% and 11.7%, 31.0% and 61.8% lower than control yields, respectively. Also, vegetative organ dry matter translocation (DMT) and its contribution to grain increased as shading levels increased under different densities. DMT increased and then decreased with increasing planting density. The dry matter assimilation amount after silking (AADMAS) increased as solar radiation and planting density increased. When solar radiation was less than 580.9 and 663.6 MJ m-2, for XY335 and ZD958, respectively, AADMAS increases were primarily related to solar radiation amounts; and when solar radiation was higher than those amounts for those hybrids, increases in AADMAS were primarily related to planting density. Photosynthate accumulation is a key determinant of maize yield, and the vegetative organs’ contributions to the grain did not compensate for the reduced yield caused by insufficient light. Between the two cultivars, XY335 showed better resistance to weak light than ZD958 did. To help guarantee high maize yield under weak light conditions it is imperative to select cultivars that have great stay-green and photosynthetic efficiency characteristics when they are grown under weak light.